Assessment of IL-18 in HCV with T2DM in Al-Najaf Province - Gihad, Zeena Kareem (Medical Science Journal for Advance Research, 2025)
The study’s objective is to look at the Hepatitis C virus in Al-Najaf province patients who have diabetes mellitus. In order to accomplish this, a total of 85 patients (44 men and 41 women) from AL-Hakeem Hospital in AL-Najaf province who were suspected of having diabetes and the hepatitis C virus, during the period from April 10, 2024, to January 5, 2025. Their age are ranged between (≥20 and ≤41). The detection of IgG specific for HCV was done by the use of third generation of ELISA technique and the Estimation of human IL-18 in serum was performed using sandwich-ELISA The study’s findings showed a significant prevalence of disease in adults, with 38% of those aged ≤41 and 26% of those aged 31–40 years having the condition. The findings showed that groups of patients with diabetes had higher levels of specific anti-HCV IgG antibodies than groups without diabetes. The percentage of HCV patients without diabetes was 82.1%, whereas the percentage of HCV patients with diabetes was 17.9%. Patients with diabetes exhibited significantly greater blood levels of IL-18 (50.3 pg/ml) than those without diabetes (control group), with a mean concentration of 5.88 pg/ml P<0.05, according to the current study. The study found a substantial difference in serum levels of IL-18 between HCV patients with diabetes and those without the disease. With a mean value of 44.97 pg/ml (P<0.05), it is clear that HCV patients with diabetes had higher blood levels of IL-18 (55.39 pg/ml) than HCV patients without diabetes.